Os Lebenshöhepunkte como ethos cristão em Hegel e Nietzsche a partir dos conceitos de "destino" e "amor" - Feiler, Adilson Felicio (2014)
Through the concepts of Love and Destiny, we present an approach between Hegel and Nietzsche, respectively in the following works: The spirit of Christianity and its fate and Antichrist. The focal point of this approach is the Christian ethos, which has as its telos, this reading of German romanticism, openness to the fullness of life: Lebensfülle, that reaches their high points: Lebenshöhepunkte. With this concept we present the Christianity linked to the Jesus s practice that includes the normative and organic aspects, by criticism of moral and law and afirmation of the Christian ethics. It is therefore achieved through approximation of differences, marked by: being and non-being, the Apollonian and the Dionysian which respectively reached reconciliation and love. Both trends point to a teleological ethical model marked by the opening of life to its fullness: Lebensfülle, which is destined to reach infinitely high points: Lebenshöhepunkte.